Selective extraction of small and large molecules from the cerebrospinal fluid by Purkinje neurons. - Borges, L; Elliott, P; Gill, R; Iversen, S; Iversen, L (1985)
Cerebellar Purkinje neurons accumulated propidium iodide, granular blue, and horseradish peroxidase conjugated to wheat germ agglutinin but not unconjugated horseradish peroxidase, bisbenzimide, or Evans blue when these compounds were infused into the lateral cerebral ventricles of awake, unrestrained rats. Accumulation of propidium iodide by Purkinje neurons of the vermis was associated with a reproducible behavioral abnormality characterized by truncal tremor, ataxia, and nystagmus. Both the accumulation of propidium iodide in Purkinje cells and the behavioral abnormality were prevented by prior intracerebroventricular administration of ouabain or colchicine, drugs that block neuronal transport processes. The ability of cerebellar Purkinje neurons to extract small and large molecules from the cerebrospinal fluid has important implications for their physiology and pathology.